Chapter 17: Sterile formulations (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
AuthorMrs. Jyoti Phogat       Assistant Professor, R. J. World College of Pharmacy Education and Technology, Jakhod, Rajasthan, IndiaAbstract: Sterile formulations are critical pharmaceutical products designed to be free from viable microorganisms, essential for parenteral administration and other applications requiring absolute sterility. This section covers various types of sterile products, including injections, ophthalmics, and large volume parenterals. The principles of sterilization, including terminal sterilization and aseptic processing, are examined in detail. Formulation considerations for sterile products, such as tonicity adjustment, pH control, and the use of preservatives in multi-dose formulations, are discussed. The manufacturing process for sterile products, including aseptic filling and lyophilization, is explored with emphasis on contamination control and validation. Clean room design and operation, including air classification and personnel gowning procedures, are addressed. Quality control measures specific to sterile formulations, such as sterility testing, endotoxin testing, and particulate matter analysis, are detailed. The challenges in developing and manufacturing sterile products, including stability issues and container-closure integrity, are discussed along with strategies to overcome them. Regulatory requirements and guidelines for sterile product manufacturing, including current Good Manufacturing Practices (cGMP), are highlighted to ensure compliance and product safety.Keywords: Aseptic processing, Parenteral preparations, Clean room technology, Sterilization, Contamination control, Regulatory compliance View PDF